Transition state theory for enzyme kinetics - Truhlar, Donald G. (Arch Biochem Biophys, 2015)
This article is an essay that discusses the concepts underlying the application of modern transition state theory to reactions in enzymes. Issues covered include the potential of mean force, the quantization of vibrations, the free energy of activation, and transmission coefficients to account for nonequilibrium effect, recrossing, and tunneling.